Reclaiming Parenthood After Incarceration: The Nexus of Determination to Desist, Fulfillment of Parental Responsibilities, and Recidivism - Liu, Lin (Criminal justice and behavior, 2023)
Prior research indicates that reclaiming family roles, such as parent or spouse, can facilitate re-entry and reintegration for justice-involved individuals. However, few studies have examined whether a determination to desist and shield children from the negative impact of crime is associated with reentry outcomes. This study examined the nexus of determination to desist, parental nurturing practices, and recidivism. Multilevel longitudinal modeling was employed to analyze respondents’ varying levels of commitment to nurturing children and recidivism risk. Results showed that returning mothers were more committed to parenting activities than returning fathers. Moreover, with the effects of prior records, reentry programs, and familial criminogenic environment controlled, we found that returning parents who were more committed to parenting had significantly lower odds of recidivism. Implications for research and policy were discussed.